Gastrodiplomacy as a Strategy for Strengthening Indonesian Cuisine in the Philippines: Opportunities and Challenges - Rulli Krisnanda; Armando Hisuan Jr; Gilang Sandhubaya; Arzendy Berlian Sabrina (Politeknik Sahid, 2026)
Gastrodiplomacy has become an important instrument in modern cultural diplomacy to strengthen nation branding through culinary arts. This study analyzes the potential of gastrodiplomacy as a strategy to strengthen the image of Indonesian food in the Philippines through culinary tourism and hospitality approaches. This study uses a qualitative-descriptive method by collecting data from recent journal literature and analyzing various gastrodiplomacy initiatives undertaken by Indonesia. The results show that the Philippines is a potential market for Indonesian culinary promotion given its geographical proximity, cultural similarities, and increasing consumer interest in authentic food. The Wonderful Indonesia, Indonesia Spice Up The World, Wonderful Indonesia Gourmet (WIG) Co-Branding Program, and the launch of the WISH 2025